A Molecular Docking Study of Human STEAP2 for the Discovery of New Potential Anti-Prostate Cancer Chemotherapeutic Candidates - Ongaba, Timothy; Ndekezi, Christian; Nakiddu, Nana (Frontiers in Bioinformatics, 2022)
Prostate cancer is a rising health concern and accounts for 3.8% of all cancer deaths globally. Uganda has one of the highest incidence rates of the disease in Africa at 5.2% with the majority of diagnosed patients found to have advanced disease. This study aimed to use STEAP2 protein (prostate cancer-specific biomarker) for the discovery of new targeted therapy. To determine the most likely compound that can bind to STEAP2 protein, we docked the modeled STEAP2 3Dstructure against 2466 FDA (Food and Drug Administration) approved drug candidates using Autodock vina. Protein Basic Local Alignment Search Tool (BLASTp) search, Multiple Sequence Alignment (MSA), and phylogenetics were further carried out to analyze the diversity of this marker and determine its conserved domains as suitable target regions. Six promising drug candidates (ligands) were identified. Triptorelin had the highest binding energy (-12.1 kcal/mol) followed by Leuprolide (docking energy:-11.2 kcal/mol). All the top two drugs candidates interacted with residues Ser-372 and Gly-369 in close proximity with the iron-binding domain (an important catalyst of metal reduction). The two drugs had earlier been approved for the treatment of advanced prostate cancer with an elusive mode of action Through this study, further insight on how their interaction with STEAP2 might be important during treatment